2007
DOI: 10.1038/sj.eye.6702980
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab (avastin) for proliferative diabetic retinopathy: 6-months follow-up

Abstract: Aims To study the effects of intravitreal bevacizumab (Avastin) on retinal neovascularization (RN) in patients with proliferative diabetic retinopathy (PDR). Methods Retrospective study of patients with RN due to PDR who were treated with at least one intravitreal injection of 1.25 or 2.5 mg of bevacizumab. Patients underwent ETDRS best-corrected visual acuity (BCVA) testing, ophthalmoscopic examination, optical coherence tomography (OCT), and fluorescein angiography (FA) at baseline and follow-up visits.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
5
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 36 publications
2
101
5
6
Order By: Relevance
“…Furthermore, Arevalo et al reported a dose-dependent response that 2.5 mg dosage seemed to be more effective than the 1.25 mg to have complete NV regression in naïve eyes. 20 Nevertheless, in a recent biologic study, a possible therapeutic effect in the fellow eye raises concern that systemic side effects are possible in patients undergoing intravitreal bevacizumab (6.2 mg-1.25 mg) treatment, and a lower dose regimen may achieve a therapeutic result with less risk of systemic side effects. 11 Further study of the optimal dosing of intravitreal bevacizumab in treating PDR is indicated.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Arevalo et al reported a dose-dependent response that 2.5 mg dosage seemed to be more effective than the 1.25 mg to have complete NV regression in naïve eyes. 20 Nevertheless, in a recent biologic study, a possible therapeutic effect in the fellow eye raises concern that systemic side effects are possible in patients undergoing intravitreal bevacizumab (6.2 mg-1.25 mg) treatment, and a lower dose regimen may achieve a therapeutic result with less risk of systemic side effects. 11 Further study of the optimal dosing of intravitreal bevacizumab in treating PDR is indicated.…”
Section: Figmentioning
confidence: 99%
“…In literature, the progression to TRD from a preexisting fibrovascular tissue contraction is a risk in few cases after intravitreal bevacizumab. 10,20,22 Furthermore, Arevalo et al reported the development or progression of TRD in 5.2% patients with severe PDR following intravitreal bevacizumab. 23 Cautious echographic examinations should be done before intravitreal bevacizumab to exclude the patients with broad vitreoretinal adhesion.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Since the Diabetic Retinopathy Vitrectomy Study over 25 years ago, there has been significant advancement in surgical techniques such as the use of a wide-angled viewing system, use of a perioperative endolaser, 4,5 small-gauge vitrectomy, and use of anti-vascular endothelial growth factor adjuvants before surgery. 6 Also, with the early diagnosis of disease from screening, one would predict that the prevalence of this end-stage condition is decreasing and the visual outcomes are improving.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled case series have demonstrated that bevacizumab could induce complete regression of neovascularization, as assessed by ophthalmoscopy and/ or fluorescein angiography, in 61.4-100 % of participants. Regression could occur as early as 1 week and as late as 1 month post-injection, with cases of recurrence 2 weeks to 3 months after initial treatment [34][35][36][37][38][39][40]. Filho et al [41] conducted a randomized controlled trial comparing PRP to PRP with ranibizumab given as a single 0.5 mg injection after the first of two laser sessions; retreatment with ranibizumab in the combined group and additional PRP in the laser only group were given at 16 and 32 weeks after baseline.…”
Section: Adjunct To Prpmentioning
confidence: 99%